2007
DOI: 10.1186/1471-2164-8-434
|View full text |Cite
|
Sign up to set email alerts
|

The TriTryp Phosphatome: analysis of the protein phosphatase catalytic domains

Abstract: BackgroundThe genomes of the three parasitic protozoa Trypanosoma cruzi, Trypanosoma brucei and Leishmania major are the main subject of this study. These parasites are responsible for devastating human diseases known as Chagas disease, African sleeping sickness and cutaneous Leishmaniasis, respectively, that affect millions of people in the developing world. The prevalence of these neglected diseases results from a combination of poverty, inadequate prevention and difficult treatment. Protein phosphorylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(121 citation statements)
references
References 131 publications
1
112
0
7
Order By: Relevance
“…As great achievements in AT have been made by using comparisons with malaria and leishmaniasis, such a comparative approach among trypanosomiases could be fruitful (62,79,146). In this context, the Tritryp project, which involves jointly analyzing genomes and proteomes of T. brucei brucei, Trypanosoma cruzi, and Leishmania major, highlights the remarkably conserved genetic core between these species (23,38,62,125). Several genome projects are also under way for T. brucei gambiense, T. congolense, and T. vivax (62).…”
Section: At and Comparative Pathologymentioning
confidence: 99%
“…As great achievements in AT have been made by using comparisons with malaria and leishmaniasis, such a comparative approach among trypanosomiases could be fruitful (62,79,146). In this context, the Tritryp project, which involves jointly analyzing genomes and proteomes of T. brucei brucei, Trypanosoma cruzi, and Leishmania major, highlights the remarkably conserved genetic core between these species (23,38,62,125). Several genome projects are also under way for T. brucei gambiense, T. congolense, and T. vivax (62).…”
Section: At and Comparative Pathologymentioning
confidence: 99%
“…Secondary structure prediction was carried out using PSIPRED Protein Sequence Analysis Workbench version 3.3 (http://bioinf.cs.ucl.ac.uk/psipred/) (Melo et al 2002;Arnold et al 2006;Shen and Sali, 2006;Bordoli et al 2009;Guex et al 2009;Buchan et al 2013;Biasini et al 2014).…”
Section: Bioinformatic Analysismentioning
confidence: 99%
“…Also, different groups have analyzed genes coding for PTPs, which has provided interesting data. The T. cruzi genome codes for only two intracellular, classical PTPs, fully dedicated enzymes for tyrosine dephosphorylation [64][65][66]. Therefore, if PTPs evolved independently several times, it is likely that protozoan enzymes display unique structural motifs or mechanism of regulation, which could allow for the development of specific chemotherapies [67].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, drugs that act by modulating signal transduction pathways are particularly interesting. Although this matter remains largely unexplored in trypanosomatids, recent work has generated promising data [60,63,64,[68][69][70]. A comparative study of the kinomes of trypanosomatids T. brucei, T. cruzi and Leishmania major showed that approximately 12% of their kinases are unique to trypanosomatids [63,69].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation